Haemophilia: Reasons for visits to the paediatric emergency department - Paula García Sánchez; Julia Martín Sánchez; María Isabel Rivas Pollmar; María Teresa Álvarez Román; Víctor Jiménez Yuste (Elsevier, 2019)
Introduction: Haemophilia is a rare disease and its management can pose a challenge to Emergency Department paediatricians. Aim: To describe the frequency and reasons for consultation by haemophilic children in the ED. Materials and methods: Longitudinal retrospective study was conducted in a paediatric Emergency Department of a tertiary care hospital. The study included haemophiliacs A and B, ages 0 to 16 years old, and who had consulted the Emergency Department for whatever reason over a span of 6 years (2011-2016). The data analysed include: age, type and severity of haemophilia, reason for query, prophylactic status, complementary examinations, established diagnosis, treatment, and number of visits to the Emergency Department. Results: The analysis included 116 males with a total of 604 Emergency Department visits. The mean age was 5.5 years, and the median age was 5.3 years. A total of 101 patients were categorised as haemophiliac A (38 mild, 4 moderate, 59 severe), and 15 as haemophiliac B (9 mild, 3 moderate, 3 severe). The main reasons for initial Emergency Department visits (ranked by triage) were: musculoskeletal problems/injury or bleeding (66.7%), causes unrelated to haemophilia (29%), suspected central venous catheter related infection (2.8%), and routine clotting factor infusion (1.5%). Additional tests were conducted during 335 visits (55.5%). Factor replacement was undertaken in 317 visits (52.5%). A total of 103 episodes (17.1%) required hospital admission, due to: head trauma (35.9%), central venous catheter -related infection (13.6%), haemarthrosis (8.7%), muscle haematoma (6.8%), and haematuria (5.8%). Conclusion: Haemophilic patients went to the Emergency Department for common paediatric causes, but also requested consultation on specific problems related to haemophilia, with musculoskeletal problems/injury or bleeding being the main issues. The paediatric Emergency Department is an indispensable component of haemophilia care. Resumen: Introducción: La hemofilia es una enfermedad rara, por lo que su abordaje en Urgencias puede suponer un reto para los pediatras. Objetivos: Describir la frecuencia y motivos de consulta de los niños hemofílicos en Urgencias. Material y métodos: Estudio retrospectivo longitudinal realizado en Urgencias Pediátricas de un hospital de tercer nivel. Se incluyeron hemofílicos A y B, desde el nacimiento hasta los 16 años, que consultaron por cualquier motivo durante 6 años (2011-2016). Se analizaron: edad, tipo y gravedad de hemofilia, motivo de consulta, profilaxis domiciliaria frente a sangrados, pruebas complementarias, diagnóstico establecido, tratamiento y número de visitas a Urgencias. Resultados: Se analizaron 116 varones con un total de 604 visitas. La media de edad fue de 5,5 años y la mediana de 5,3. De ellos, 101 pacientes eran hemofílicos A (38 leves, 4 moderados, 59 graves) y 15 hemofílicos B (9 leves, 3 moderados, 3 graves). Los principales motivos de consulta (clasificados en triaje) fueron: problema musculoesquelético/traumático o sangrado (66,7%), causas no relacionadas con hemofilia (29%), sospecha de infección de catéter central (2,8%) y administración rutinaria de factor (1,5%). Se realizaron pruebas complementarias en 335 visitas (55,5%). Del total, 317 consultas (52,5%) requirieron factor; 103 episodios (17,1%) precisaron ingreso, cuyos principales motivos fueron: traumatismo craneoencefálico (35,9%), infección de catéter venoso central (13,6%), hemartrosis (8,7%), hematoma muscular (6,8%) y hematuria (5,8%). Conclusión: Los pacientes consultaron por causas habituales de la edad pediátrica, pero también lo hicieron por motivos específicos de su enfermedad; lo más frecuente fue el problema musculoesquelético/traumático o sangrado. El Servicio de Urgencias es un componente indispensable en su atención.